Przyszłość językowa Unii Europejskiej: mit wielojęzyczności czy dominacja języka angielskiego? - Borowiak, Marta (Investigationes Linguisticae, 2008)
On the threshold of the 21st century when another 12 states joined the European Union a matter of multilingualism has been recently considered as a crucial factor with regard to European integration process. Having diverse society the UE has started to promote a phrase Unity in Diversity which in turn provides patronage for a number of cultural and education campaigns. Their aim is to prepare the European citizens for cultural integration and to help them to create a sense of European identity. The main assumption of the already taken actions is taking multilingualism as the pillar of the Union and presenting it as an example of equality regardless to citizens’ nationality. The herby article reveals however, that the idea of unity in diversity – at least from the linguistic point of view – is practically impossible to accomplish especially in the face of such a strong position of English in the international arena as it has nowadays. What’s more, inside Union in its administration structures the idea of equality is not observed. Due to purely practical and organisational reasons just one language is used – English. Also English is the foreign language that is taught most often in schools throughout the Europe. A question arises whether the idea of a multilingual Union is not a myth?